Integrasi Canva Sebagai Media Presentasi Kolaboratif Dalam Pembelajaran Matematika - Ni Wayan Ulandari; Ketut Agustini; I Gde Wawan Sudatha (Jayapangus Press, 2026)
This study systematically reviews the use of Canva in mathematics learning, focusing on integration strategies, its role as a collaborative presentation media, its contribution to students’ creativity and presentation skills, and its impact on learning outcomes. A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines, with 28 eligible articles analyzed thematically. The synthesis reveals that Canva is effective when implemented through structured planning, implementation, and evaluation, and when used to enhance visual representation and mathematical communication. Canva also supports the development of visual creativity, presentation skills, conceptual understanding, and learning motivation. However, this review identifies limited longitudinal studies and a lack of research at the senior high school level. Conceptually, these findings highlight visual digital media as a pedagogical mechanism in 21st-century mathematics learning, while practically emphasizing the importance of task design, teacher facilitation, and students’ digital literacy readiness.